Effect of PDT, and new chelating solutions on inactivation of bacterial LPS - Oda, Denise Ferracioli (2021)
INTRODUCTION: In the necropulpectomies, in addition to the elimination of microorganisms and to neutralization of lipopolysaccharides (LPS), present in root canal system, it is fundamental, since that endotoxin is highly related to unsuccessful cases with painful symptomatology. OBJECTIVE: The present study evaluated the capacity of Photodynamic Therapy (PDT) and the different irrigants, to inactivate the bacterial LPS. MATERIALS AND METHODS: Eighty single-rooted human teeth were used, previously analyzed by radiographic images to confirm the single canal. The coronary portion was removed to obtain 14mm segment of the root, where the canals were properly prepared. The samples were placed vertically in 24-well plates and fixed with acrylic resin. The samples and all the materials used in the study were previously sterilized with Cobalt-60 Gamma radiation. Inside the laminar flow cabinet, 10L of LPS from Escherichia coli were inoculated inside in root canal of each sample and kept for 24 hours in a bacteriological oven. The inoculation procedure was repeated twice more and then the samples were divided into the following groups (n = 10): [G1] sodium hypochlorite at 2.5%; [G2] pyrogen-free water; [G3] trisodium EDTA at 17%; [G4] tetrasodium EDTA at 10%; [G5] Etidronate at 18%; [G6] Methylene blue at 5%; [G7] diode LASER; [G8] PDT (methylene blue + diode LASER). The time for action of the irrigating solutions, dye and irradiation, was 5 minutes for all groups. After the treatment, the canals were cleaned and filled with 5mL of pyrogen-free water, where it was agitated and aspirated by a pyrogen-free needle/syringe. The aspirated content of each specimen was kept under refrigeration at -80ºC until posterior analysis of Limulus Amebocyte Lysate. The obtained data did not pass the Shapiro Wilks normality test, so they were submitted to the Kruskal-Wallis test followed by the Dunns test. RESULTS: The obtained data presented relevant reduction only in the groups G3 (p = 0.0452) and G5 (p = 0.0097), in comparison to the control group G2. The medium percentage (Minimum/Maximum) of remaining endotoxin was: [G1] = 1.005 (0.3100/5.810); [G2] = 2.010 (0.8700/10.33); [G3] = 0.3800 (0.060 /2.150); [G4] = 1.195 (0.110/3,420); [G5] = 0.9000 (0.0/1.540); [G6] = 1.320 (0.1800/9.410); [G7] = 1.210 (0.4700/9.400); [G8] = 3.560 (0.4800/5.460).CONCLUSION: The PDT did not present efficacy in neutralizing the LPS and, among the evaluated solutions, trisodium EDTA at 17% and etidronate at 18% presented efficacy in inactivating the bacterial endotoxin.